2007
DOI: 10.1159/000111489
|View full text |Cite
|
Sign up to set email alerts
|

To Continue, Modify or Relinquish Driving: Findings from a Longitudinal Study of Healthy Ageing

Abstract: Background: The number and proportion of drivers among people entering later life continues to rise. More information on patterns of driving for older adults is required to improve service provision and traffic planning. Objectives: To map the changes in driving status for a sample of drivers aged 65 years or older over the period 1994–2000, and to identify factors associated with older people continuing, modifying or relinquishing their status as drivers. Methods: The 752 participants were drawn from the Melb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 33 publications
3
41
2
1
Order By: Relevance
“…11 Reported self-regulatory behavior increases with age and becomes even more pronounced with declining health status, suggesting that elderly drivers are in fact attempting to compensate for perceived functional impairments. [16][17][18][19][20] Consistent with this notion, several survey studies have reported increased driving restriction among older drivers that is at least partly in response to the presence of cognitive or functional impairment. 9,12,[20][21][22][23][24] In a 5-year longitudinal study in which older drivers were interviewed yearly about driving habits, drivers categorized as at-risk on the basis of reduced Useful Field of View performance were found to limit their driving mobility over time at a faster rate than those categorized as not-at-risk drivers.…”
Section: Introductionmentioning
confidence: 75%
“…11 Reported self-regulatory behavior increases with age and becomes even more pronounced with declining health status, suggesting that elderly drivers are in fact attempting to compensate for perceived functional impairments. [16][17][18][19][20] Consistent with this notion, several survey studies have reported increased driving restriction among older drivers that is at least partly in response to the presence of cognitive or functional impairment. 9,12,[20][21][22][23][24] In a 5-year longitudinal study in which older drivers were interviewed yearly about driving habits, drivers categorized as at-risk on the basis of reduced Useful Field of View performance were found to limit their driving mobility over time at a faster rate than those categorized as not-at-risk drivers.…”
Section: Introductionmentioning
confidence: 75%
“…Several studies have reported that older drivers selfregulate their driving in certain driving situations, for example by driving slower or by reducing the time and distance driven [3,5] . Moreover, older drivers seem to compensate for distractions by driving slower in complex traffic environments [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The car enables mobility and access to essential services and social activities [2][3][4] . Consequently, most older drivers continue to drive as they age [5] . However, the complex interaction between sensory, cognitive and perceptual-motor processes required for safe driving are vulnerable due to the inherent changes that come with age [6] .…”
mentioning
confidence: 99%
“…This may be due to the adoption of compensatory strategies similar to those used by elderly drivers, although there is no direct evidence of this in stroke patients (De Raedt & Ponjaert-Kristoffersen, 2000;Fisk et al, 1997;George, Clark & Crotty, 2006;Unsworth, Wells, Browning, Thomas & Kendig, 2008). Older drivers who learn and use compensatory strategies such as avoiding peak hour traffic, driving in daylight and driving only in familiar areas, can reduce their accident level to that of, or lower than, technically better drivers (De Raedt & Ponjaert-Kristoffersen, 2000).…”
Section: Introductionmentioning
confidence: 99%